Clinical trials : design, conduct, and analysis - Meinert, Curtis L. (New York : Oxford University Press, 2012)
"First published in 1986, this landmark text is the definitive guide to clinical trials, written by one of the leading experts in the field . This fully-updated second edition continues to be the most authoritat ive reference text on randomized clinical trials. It contains a wealth of practical information on the design, conduct, and analysis of both s ingle center and multicenter trials. No other book on clinical trials o ffers as much detail on such issues as sample size calculation, stratif ication and randomization, data systems design, development of consent forms, publication policies, preparation of funding requests, and repor ting procedures. While the basics of design, conduct, and analysis of c linical trials remain the same, there have been significant changes sin ce the first edition of Clinical Trials was published two decades ago. In this new edition, the author discusses the refinements and improveme nts made to methods and procedures, changes in the policies and guideli nes underlying trials, as well as requirements for registration of tria ls. He also discusses current practices for data sharing, for gender re presentation, for treatment effects monitoring, and for ethical standar ds of clinical trials. The importance of the randomized controlled tria l has grown significantly over time and they are now the cornerstone of all evidence-based medicine. Still rich in tables, checklists, charts, and other resources for the trialist, the second edition of Clinical T rials is an indispensable reference for clinicians, biostaticians, epid emiologists, and anyone involved in the design and implementation of a clinical trial"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Clinical trials; Clinical Trials as Topic